2015
DOI: 10.3892/or.2015.4016
|View full text |Cite
|
Sign up to set email alerts
|

HtrA1: Its future potential as a novel biomarker for cancer

Abstract: HtrA1 appears to be involved in several physiological processes as well as in the pathogenesis of conditions such as Alzheimer’s disease and osteoarthritis. It has also been hypothesized to play a role as a tumor suppressor. This manuscript reviews the current cancer-related HtrA1 research from the methodological and clinical standpoints including studies regarding its potential role as a tumor marker and/or prognostic factor. PRISMA method was used for study selection. The articles thus collected were examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 52 publications
(83 reference statements)
1
18
0
Order By: Relevance
“…However, the present data do suggest that HtrA1 may provide an important link between UCL and CRC, and that epithelium and stroma are differentially affected (41). Notably, it has been suggested that HtrA1 responds to different environments in different ways, probably due to its secretory characteristic (42), and that high HtrA1 levels are associated with chronic inflammatory conditions such as rheumatoid arthritis, osteoarthritis and macular degeneration (26,27,(43)(44)(45). The latter data appear to contrast with the decreased HtrA1 expression found in UCL, where patterns were similar to those observed in CRC.…”
Section: Low High Expression Expression -----------------------------mentioning
confidence: 45%
See 1 more Smart Citation
“…However, the present data do suggest that HtrA1 may provide an important link between UCL and CRC, and that epithelium and stroma are differentially affected (41). Notably, it has been suggested that HtrA1 responds to different environments in different ways, probably due to its secretory characteristic (42), and that high HtrA1 levels are associated with chronic inflammatory conditions such as rheumatoid arthritis, osteoarthritis and macular degeneration (26,27,(43)(44)(45). The latter data appear to contrast with the decreased HtrA1 expression found in UCL, where patterns were similar to those observed in CRC.…”
Section: Low High Expression Expression -----------------------------mentioning
confidence: 45%
“…HtrA1 plays a pivotal role in the fibroblast growth factor pathway, downregulating tumour progression (24). Changes in its expression have been reported in conditions such as osteoarthritis, age-related macular degeneration and cancer (25)(26)(27). It tends to be downregulated in the metastatic foci of various tumours compared with the primary tumour in a number of malignancies, such as melanoma, sarcoma, neuroblastoma and lung cancer (23,24), while its overexpression has been hypothesized to inhibit growth and proliferation processes by acting on tumour cell apoptosis, invasiveness and migration (28).…”
Section: Introductionmentioning
confidence: 99%
“…There were 25 duplicates (figure 1); 214 papers were excluded because 28 were conference posters, 54 were reviews, 84 regarded other subjects, 30 were animal, in vitro or laboratory technique studies, and 18 evaluated blood/serum/plasma or other tissues. Examination of the remaining 50 papers in the second stage of the PRISMA flow chart led to the exclusion of 31studies for the following reasons: 5 were reviews 1,19,42-44, one assessed animals 45, 5 involved laboratory technique validation 21, 46-49, one was a molecular biology study 50, 4 were survival analysis studies 51-54, 7 assessed the impact of dietary habits 57-61, 5 did not examine urine 62-66, one reported aggregate data for CRC, gastric cancer and pancreatic cancer 67, and finally 2 did not match the inclusion criteria 68,69.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, endometriosis shows close similarities with neoplastic processes represented by invasion of normal tissues and metastatic growth. It is known that HtrA1 is reduced in tumours exhibiting an higher degree of malignancy, 24 , 27 , 35 suggesting an involvement of this protein in invasive processes. Interestingly, the decrease of HtrA1 in endometriosis may be a mechanism involved in the displacement of endometrial tissue outside the uterus.…”
Section: Discussionmentioning
confidence: 99%